Direct Observations of North Pacific Subsurface Low Potential Vorticity Water Impinging on the Kuroshio - Ran Wang; Qiang Ren; Feng Nan; Fei Yu; Zifei Chen; Yansong Liu; Jianfeng Wang; Chuanzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiaohua Zhu (Geophysical Research Letters)
Abstract In this study, for the first time, we found a Subsurface Low Potential Vorticity Water (SLPVW) to the east of Taiwan Island (122°–124°E, 21.67°–23°N) via an array comprising 12 current and pressure‐recording inverted echo sounders (CPIESs) from 25 June 2018 to 29 July 2019. This SLPVW exhibits remarkable intraseasonal variability, with an ∼100‐day period east of Taiwan Island, corresponding with the variability in mesoscale eddies. Compared with large‐scale climatological mean circulation, mesoscale eddy can trap SLPVW as a highway westward transport. In addition, the SLPVW impingement results in a significant subsurface velocity variation (about 10 cm/s) in the 200–400 m layer. These findings shed new light on the mechanisms of the intraseasonal variation in the Kuroshio subsurface layer.